Attaining the Public Diplomacy Goals of U.S. Exchange Programmes in Vietnam - Le, Thi Ly (2024)
Exchange diplomacy is a central element of public diplomacy. Compared to other one-way public diplomatic tools like listening, advocacy, and international broadcasting, this two-way channel has proved more advantageous as it engages with non-state actors through direct communication with minimal control from government sponsors. Hence, this tool is trusted to build and sustain relationships between the people of countries hosting and sending exchangers. The U.S. government’s sponsorship of exchange programmes has been motivated by the notion that exchange experiences (experiences) would boost mutual understanding between the people of the U.S. and the people of other countries (knowledge), enable greater tolerance of one another (attitude), and ultimately foster collaborative relationships between the U.S. and countries worldwide (behaviour). The U.S. government launched its first exchange programme in Vietnam in 1992, when its bilateral relations with Vietnam were still fragile, and has since persisted in making exchange diplomacy a core element of its strategy to soften, build, and advance its relations with Vietnam. Although U.S. exchange diplomacy has long been operational in Vietnam, the extent of its impact remains unknown. In the broader literature on exchange diplomacy evaluation, the assumption that exchange experiences induce a sequence of positive changes among exchange alumni has not yet been fully verified. Existing studies lack sufficient rigour to tackle the common challenges faced in exchange impact assessment, such as abstract and hierarchical concepts and intangible and mediated impacts. Accordingly, this thesis aims to test the attainment of the public diplomacy goals of U.S. exchange diplomacy in Vietnam by applying the knowledge-attitude-behaviour (KAB) theoretical model and the structural equation modelling (SEM) technique.